THE ARABIC ORIGINS OF ENGLISH AND INDO-EUROPEAN "URBAN TERMS": A RADICAL LINGUISTIC THEORY APPROACH - Zaidan Ali Jassem (English Review: Journal of English Education, 2015)
Abstract: This paper traces the Arabic origins of English, German, French, Latin, Greek, and Sanskrit "urban terms" from a radical linguistic (or lexical root) theory perspective. The data comprises 130 such terms like abide, building, city, construction, courtyard, hotel, house, live, mansion, mason,Â  palace, metropolis, residence, road, rural, sedentary, sojourn, stay, structure, tent, town, urban, villa, village, zoo, and so on. The results clearly show that all such words have true Arabic cognates with the same or similar forms and meanings, whose differences are due to natural and plausible causes and different routes of linguistic change. Moreover, the results support the adequacy of the radical linguistic theory according to which, unlike the Comparative Method and/or Family Tree Model, Arabic, English, German, French, Latin, Greek, and Sanskrit are dialects of the same language or family, renamed Eurabian or Urban family, with Arabic being their origin all for sharing the whole cognates with them and for its huge phonetic, morphological, grammatical, and lexical variety and wealth. Also, they indicate that there is a radical language from which all human languages stemmed and which has been preserved almost intact in Arabic as the most conservative and productive language, without which it is impossible to interpret its linguistic richness and versatility on all levels. Â Keywords: urban terms, Arabic, English, German, French, Latin, Greek, Sanskrit, historical linguistics, radical linguistic (lexical root) theory, language relationshipsÂ